1992
DOI: 10.1002/stem.5530100603
|View full text |Cite
|
Sign up to set email alerts
|

CD4 activation of HIV fusion

Abstract: The primary cellular receptor for the human immunodeficiency viruses type 1 (HIV-1) and type 2 (HIV-2) is the CD4 antigen. HIV infection of CD4+ cells is initiated by binding of the virus to the cell surface, via a high affinity interaction between CD4 and the HIV outer envelope glycoprotein, gp120. The development of model systems using soluble recombinant forms of CD4 (sCD4) has allowed kinetic and thermodynamic analyses of CD4 binding to gp120, and study of the post-binding events leading to virus-cell memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…However, a recent study by Moore and co-workers8 indicated that among the constant domains of gpl20env only the Cl and a portion of C4 seem to be accessible to MAb on native monomeric molecule. Although C2 was considered to be poorly accessible, we wished to analyse the antigenicity of a particular region extending from residue 273 to 288 (EEVVIRSAN-FTDNAKT) because there are several lines of evidence suggesting that this region plays a role in the early events of viral infection: (1) We have previously reported that the lectin jacalin, which binds to CD4 and inhibits HIV infection, shows a 14 amino acid peptide presenting high similarities (8 common residues and 2 conservative charges) with the amino acid sequence 273-288 of the C2 domain of gp\2(„nv. This peptide (VVVRSLTFKTNKKT), at high concentration, demonstrated antiviral properties on some HIV-1 isolates.9 (2) It has also been reported10 that the vasoactive intestinal peptide (VIP), which has been claimed to interact with CD4,11 presents a fragment ' of high similarity (5 identical residues and 1 conservative charge) with this gpl20 sequence (HSDAVFTDNYTR); this peptide has been shown to antagonize in vitro neuronal cell death induced by gpl20c"v.12 (3) The antiviral property of another peptide (ASTTTNYT) showing similarities with the gpl20e"v region extending from residue 280 to 287 has been reported.13 (4) Apart from the information derived from the peptide approach, other results obtained from mutagenesis suggest an involvement of this region in HIV-1 infection: The 286A/V mutation is responsible for the generation of an escape mutant virus insensitive to anti-V3 MAb neutralization, suggesting that this region may interact with V3 or indirectly affect the structure of V3.14 The 284 D/N mutation alters the association of gpl20env' with gp41e"v and this mutant virus has lost its infectivity.15 (6) Finally, a mutant virus expressing the double mutation 283 T/M and 287 K/V is insensitive to soluble CD4 (sCD4) treatment.16…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Moore and co-workers8 indicated that among the constant domains of gpl20env only the Cl and a portion of C4 seem to be accessible to MAb on native monomeric molecule. Although C2 was considered to be poorly accessible, we wished to analyse the antigenicity of a particular region extending from residue 273 to 288 (EEVVIRSAN-FTDNAKT) because there are several lines of evidence suggesting that this region plays a role in the early events of viral infection: (1) We have previously reported that the lectin jacalin, which binds to CD4 and inhibits HIV infection, shows a 14 amino acid peptide presenting high similarities (8 common residues and 2 conservative charges) with the amino acid sequence 273-288 of the C2 domain of gp\2(„nv. This peptide (VVVRSLTFKTNKKT), at high concentration, demonstrated antiviral properties on some HIV-1 isolates.9 (2) It has also been reported10 that the vasoactive intestinal peptide (VIP), which has been claimed to interact with CD4,11 presents a fragment ' of high similarity (5 identical residues and 1 conservative charge) with this gpl20 sequence (HSDAVFTDNYTR); this peptide has been shown to antagonize in vitro neuronal cell death induced by gpl20c"v.12 (3) The antiviral property of another peptide (ASTTTNYT) showing similarities with the gpl20e"v region extending from residue 280 to 287 has been reported.13 (4) Apart from the information derived from the peptide approach, other results obtained from mutagenesis suggest an involvement of this region in HIV-1 infection: The 286A/V mutation is responsible for the generation of an escape mutant virus insensitive to anti-V3 MAb neutralization, suggesting that this region may interact with V3 or indirectly affect the structure of V3.14 The 284 D/N mutation alters the association of gpl20env' with gp41e"v and this mutant virus has lost its infectivity.15 (6) Finally, a mutant virus expressing the double mutation 283 T/M and 287 K/V is insensitive to soluble CD4 (sCD4) treatment.16…”
Section: Introductionmentioning
confidence: 99%
“…The human immunodeficiency virus type 1 (HIV-1) infection pathway involves a sequential process whereby reversible binding to the CD4 receptor induces a conformational change in the viral gp120-gp41 trimeric complexes that exposes or induces formation of previously inaccessible epitopes in both gp120 and gp41 and dramatically enhances gp120 affinity for a coreceptor (46,57,65,69,71,73,75). Energetic studies have suggested that the gp120 subunit has a high entropy or conformational flexibility that inhibits binding of antibodies or other ligands and that binding to CD4 substantially reduces this flexibility, thus enhancing the subsequent binding of gp120 to additional ligands by an energetic (entropic) mechanism (36,47).…”
mentioning
confidence: 99%
“…During the course of viral infection, gp120 and gp41 are involved in the fusion process between membranes of HIV-1 and host cells expressing CD4 and certain coreceptors (2,4,13,(15)(16)(17). After receptor binding, structural rearrangements of the gp41 subunit are thought to play a role in membrane fusion (23,31,39,40) in a poorly understood process which has often been compared to that used by the hemagglutinin HA2 protein of influenza (7,9,54).…”
mentioning
confidence: 99%